Pengembangan Media Edukasi Game berbantuan Wordwall pada Evaluasi Mata Pelajaran Pendidikan Pancasila Kelas VI di SD - Fitri, Adela Khalisa; Zuardi, Zuardi (Asian Journal of Early Childhood and Elementary Education, 2025)
The development of Wordwall-assisted educational game media was carried out to address the low engagement, interest, motivation, and learning outcomes of students in Pancasila Education at SD Negeri 36 Payakumbuh. This media was selected for its user-friendliness, alignment with technological developments, and potential to enhance learning activity. The study aimed to produce a valid, practical, and effective learning medium. The research employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), with Grade V students as the research subjects. Instruments included validation sheets (by content, media, and language experts), practicality questionnaires (for teachers and students), and effectiveness tests (learning outcomes tests and learning activity questionnaires). The results indicated that: (1) content expert validity reached 94%, media expert 83%, and language expert 87%, all within the “highly valid” category; (2) teacher practicality was 95.75% and student practicality 93.96% classified as “very practical”; (3) learning activity effectiveness was 91.17%—“very effective”; and (4) post-test scores were higher than pre-test scores, indicating improved learning outcomes. Thus, the Wordwall-assisted educational game media met the criteria of being valid, practical, and effective, and is suitable for enhancing learning activity and outcomes in Pancasila Education at the elementary level.